2010
DOI: 10.1073/pnas.1006925107
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of maize detritus and a transgenic insecticidal protein (Cry1Ab) within the stream network of an agricultural landscape

Abstract: Widespread planting of maize throughout the agricultural Midwest may result in detritus entering adjacent stream ecosystems, and 63% of the 2009 US maize crop was genetically modified to express insecticidal Cry proteins derived from Bacillus thuringiensis. Six months after harvest, we conducted a synoptic survey of 217 stream sites in Indiana to determine the extent of maize detritus and presence of Cry1Ab protein in the stream network. We found that 86% of stream sites contained maize leaves, cobs, husks, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 44 publications
2
114
2
Order By: Relevance
“…detritus and grasses (Menninger and Palmer 2007;RosiMarshall et al 2007;Griffiths et al 2012a); however, unlike leaf fall, which is fairly predictable, inputs of crop detritus are sporadic and are driven by the dynamics of wind and overland flow Jensen et al 2010;Tank et al 2010) and do not appear to be pulsed in such a way as to elicit a strong temporal response in ER. In addition, input of senescent grasses occurs in late autumn, but live grasses slump into and decompose within streams throughout the year (Menninger and Palmer 2007) and may be a temporally consistent allochthonous resource to agricultural streams.…”
Section: Resultsmentioning
confidence: 99%
“…detritus and grasses (Menninger and Palmer 2007;RosiMarshall et al 2007;Griffiths et al 2012a); however, unlike leaf fall, which is fairly predictable, inputs of crop detritus are sporadic and are driven by the dynamics of wind and overland flow Jensen et al 2010;Tank et al 2010) and do not appear to be pulsed in such a way as to elicit a strong temporal response in ER. In addition, input of senescent grasses occurs in late autumn, but live grasses slump into and decompose within streams throughout the year (Menninger and Palmer 2007) and may be a temporally consistent allochthonous resource to agricultural streams.…”
Section: Resultsmentioning
confidence: 99%
“…By-products from GM plants (e.g., pollen, detritus) can be transported in water courses to downstream water bodies where non-target aquatic arthropods can be exposed to transgene product(s) through consumption (Axelsson et al, 2010(Axelsson et al, , 2011. In the case of Bt-maize, Rosi-Marshall et al (2007) reported that by-products of Bt-maize enter headwater streams in the United States and claimed, on the basis of experimental data obtained under lower-tier conditions, that this would reduce growth and increase mortality of some non-target aquatic arthropods, especially trichopteran species (see also Chambers et al, 2010;Tank et al, 2010).…”
mentioning
confidence: 99%
“…While deposition of Bt plant tissue in the proximity of streams by wind and surface runoff can result in leaching of Bt toxins in the water (Tank et al 2010;Viktorov 2011), their insecticidal properties on aquatic insects have not been demonstrated. The effect of transgenic Bt crop detritus on aquatic ecosystems should be comprehensively explored.…”
Section: Effects Of Bt Crops On Non-target Organismsmentioning
confidence: 99%